Vesicular stomatitis virus glycoprotein is anchored in the viral membrane by a hydrophobic domain near the COOH terminus - Rose, J. K. (1980)
We have determined the COOH-terminal and NH(2)-terminal amino acid sequences of the vesicular stomatitis virus (VSV) glycoprotein (G). A sequence of 122 COOH-terminal amino acids was deduced from the complete sequence of a cloned DNA insert carrying 470 nucleotides derived from the 3′ end of the G mRNA. Evidence presented indicates that this portion of the polypeptide includes the domains of G that reside inside the virion and span the lipid bilayer of the virion. This seems clear because a partial amino acid sequence of a fragment of G that remains associated with the membrane of the virion after exhaustive proteolytic digestions can be located unambiguously in the predicted sequence. This predicted sequence contains an uninterrupted hydrophobic domain beginning 49 amino acids and ending 30 amino acids from the COOH terminus. This region presumably spans the lipid bilayer. The COOH-terminal portion of 29 amino acids contains a high proportion of basic residues and resides inside the virion. The COOH-terminal portion of the VSV G protein therefore resembles in structure that of glycophorin, an erythrocyte membrane protein well characterized previously. The configuration of G in the viral membrane demonstrated here is probably similar for other viral glycoproteins, although this has not been tested as directly in any other case. From the sequence of a DNA primer extended on the RNA genome from the adjacent M protein gene into the G protein gene, we have deduced an NH(2)-terminal G protein sequence of 53 amino acids, including the leader sequence of 16 amino acids. Our sequence confirms, extends, and corrects two partial amino acid sequences reported for this region previously.